Evaluation of the Early Childhood Health and Nutrition Program: Current Issues at the Tajuncu Community Health Center, Soppeng Regency - Santri Leztari; Erni Angraeni; Sukmawati; Eny Pharamitha; Maswati; Mirnawati; Ayu; Rahmasari; Yul Inggriani (Journal of Creative Power and Ambition (JCPA), 2026)
Health and nutrition of early childhood are fundamental pillars supporting physical growth, cognitive development, and long-term child well-being. This study aims to comprehensively evaluate the implementation of health and nutrition programs for early childhood at Puskesmas Tajuncu, Donri-Donri District, Soppeng Regency, South Sulawesi, and identify current issues emerging in field implementation. The study employed a qualitative descriptive approach with data collection through in-depth interviews with the Head of Nutrition at Puskesmas Tajuncu, field observation, and documentation of child growth data from Posyandu Kemiri 1 as source triangulation. Data were analyzed using interactive analysis techniques involving data reduction, data presentation, and conclusion drawing. Results show that health and nutrition programs have been routinely implemented through monthly Posyandu activities and early detection of growth and development at PAUD/TK. Programs implemented include anthropometric monitoring (weight, height, head circumference, upper arm circumference), local supplementary food provision for 90 days, vitamin distribution, immunization, and parental nutrition counseling. Posyandu Kemiri 1 data over three months (January-March 2026) showed gradual improvement in all growth indicators. However, current issues identified include: only 50% of children achieved standard weight gain per month; 96 children with stunting and 12 with undernourishment; and inconsistent child attendance at Posyandu. Determinant factors include parenting patterns, socioeconomic conditions, and environmental sanitation. Community participation rate of 80% constitutes significant social capital. This study concludes that strengthening multisectoral collaboration among Puskesmas, Posyandu, PAUD, families, and local government is the key strategy for sustainably optimizing early childhood health and nutrition.